Search for flavour-changing neutral current top-quark decays to [Formula: see text] in [Formula: see text] collision data collected with the ATLAS detector at [Formula: see text] TeV - Aad, G; Abbott, B; Abdallah, J; Abdinov, O; Aben, R; Abolins, M; AbouZeid, O S; Abramowicz, H; Abreu, H; Abreu, R; Abulaiti, Y; Acharya, B S; et al. (The European physical journal. C, Particles and fields, 2016)
A search for the flavour-changing neutral-current decay [Formula: see text] is presented. Data collected by the ATLAS detector during 2012 from proton-proton collisions at the Large Hadron Collider at a centre-of-mass energy of [Formula: see text] TeV, corresponding to an integrated luminosity of 20.3 fb[Formula: see text], are analysed. Top-quark pair-production events with one top quark decaying through the [Formula: see text] ([Formula: see text]) channel and the other through the dominant Standard Model mode [Formula: see text] are considered as signal. Only the decays of the Z boson to charged leptons and leptonic W boson decays are used. No evidence for a signal is found and an observed (expected) upper limit on the [Formula: see text] branching ratio of [Formula: see text] ([Formula: see text]) is set at the 95 % confidence level.